Key to Identify Insects from Droppings of Some Insectivorous Bats of Nepal - Pokhrel, Santosh; Budha, Prem B. (Journal of Institute of Science and Technology, 2015)
Food habit of insectivorous bats was studied using fecal analysis. The fresh bat dropping samples from Mahendra cave, Pokhara and Nagarjun cave, Kathmandu were collected in March and September 2011. Bat droppings were moistened in hot water, separated into fine pieces and observed under stereoscope. The recovered insects and insect parts were mounted in slide, photographed and identified up to Order and Family level. Altogether ten insect orders viz. Coleoptera, Diptera, Hemiptera, Homoptera, Odonata, Hymenoptera, Lepidoptera, Orthoptera, Trichoptera and Thysanoptera and 25 families were identified. In addition, spider and mites were also reported. The identification key to Order and Family level has been prepared based on the studied characters compared with taxonomic characters from literature. Journal of Institute of Science and Technology, 2014, 19(1): 129-136